42 Atrial fibrillation and long-term survival in south asians: insights from the UK ACALM registry. (May 2019) - Potluri, Rahul; Bainey, Kevin; Bhatt, Deepak; Morillo, Carlos; Patel, Billal; Chalil, Shajil; More, Ranjit
Abstract : Background: Atrial Fibrillation (AF) is the most common cardiac arrhythmia and is an independent risk factor for mortality. However, the impact of race has not been fully explored. We evaluated the frequency, clinical characteristics, and long-term survival in South Asian and Caucasian White patients with AF using a 'big data' approach. Methods: Using the United Kingdom (UK) Algorithm for Co-morbidity, Associations, Length of stay, and Mortality (ACALM) registry, we analyzed 1, 816, 230 adults hospitalized between January 2000 and July 2014 using ICD-10 and OPCS-4 coding systems. Ethnic status was identified and AF patients were selected. Using logistic regression, we examined the odds of mortality adjusted for demographics and co-morbid status. Results: In our large cohort, South Asian patients had a lower frequency of AF hospitalization compared with Caucasian White patients (0.8% [1876/243, 363] versus 4.5% [51, 576/1, 151, 222], p=<0.001). Differences in demographics and baseline characteristics are highlighted in the table below. Kaplan-Meier survival was worse in Caucasian White patients with AF (figure 1 ). Following adjustment, White race was associated with a higher long-term mortality compared with South Asian ethnicity in patients with AF (HR 1.38, 95% CI 1.26–1.51, p<0.001). Conclusion: In a 'big data' UK registry, AF hospitalization in South Asians appears less common and is associated with improved survival compared with Caucasian White patients. Further investigation is required to understand the impact of race on AF prevalence and outcomes. Conflict of Interest: Nil